Catalyst for preparing N-(3-aminopropyl) cyclohexylamine through hydrogenation of nitrile ethyl cyclohexylamine as well as preparation method and application of catalyst

By designing a catalyst including CO, MG and alumina, the catalyst is a one-dimensional hollow nanopotranskin structure, which solves the harsh condition of N- (3-amino propyl) clock in existing technologies and insufficient catalyst stability. The problem has achieved efficient, selective and stable synthetic effects.

CN119368180APending Publication Date: 2025-01-28ZHEJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473959.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently synthesize N-(3-aminopropyl)cyclohexylamine under mild conditions, and the catalyst stability and selectivity are insufficient, and an inorganic base is required to be added during the reaction, and the pressure is high.

Method used

Catalysts including CO, Mg and alumina are used. The catalyst is a one -dimensional hollow nanopotranskin structure. Through specific synthetic methods and conditions, the activity, selectivity, and stability of the catalyst is improved.

Benefits of technology

Achieve efficient catalytic 腈 ethyl cyclolarine hydrogenation of n-(3-amino propylene) cycamine under the mild conditions. The catalyst has high activity, high selectivity and high stability, reducing the synthesis process in the process of synthesis process cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368180A_ABST
    Figure CN119368180A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing N-(3-aminopropyl) cyclohexylamine through nitrile ethyl cyclohexylamine hydrogenation and a preparation method and application thereof.The catalyst comprises an active component, an auxiliary component and a carrier, the active component is Co, the auxiliary component is Mg, the carrier is aluminum oxide, and the catalyst is of a one-dimensional hollow nanotube structure. The catalyst provided by the invention has the advantages of simple preparation method, high catalyst activity, good selectivity and good stability. In the hydrogenation reaction process of nitrile ethyl cyclohexylamine, the catalyst has high activity under mild reaction conditions. And the catalyst system shows excellent catalytic hydrogenation activity, selectivity and stability under the condition that alkali does not need to be additionally introduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic amine synthesis, and in particular to a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenating nitrileethylcyclohexylamine, and a preparation method and application thereof. Background Art

[0002] In the chemical industry, N-(3-aminopropyl)cyclohexylamine is an important intermediate widely used in the field of organic synthesis. Because it contains amino and cyclohexyl groups, it can participate in a variety of chemical reactions to generate compounds with specific functions. These compounds have broad application prospects in the fields of medicine, pesticides, materials science, etc. For example, N-(3-aminopropyl)cyclohexylamine is a selective and competitive inhibitor of spermidine synthase. N-(3-aminopropyl)cyclohexylamine can be used in the study of neurological diseases; in the polyester industry, it can be used as a curing agent to improve material properties. As its application value continues to be discovered, researchers continue to explore its efficient synthesis methods.

[0003] Patent CN 118307416 A reports a method for directly synthesizing N-(3-aminopropyl)cyclohexylamine in one step using supported nickel and cobalt as catalysts with acrylonitrile, cyclohexylamine and hydrogen. However, the products vary greatly at different temperatures, and the catalyst has not been tested for stability. Inorganic bases need to be added during the reaction, and the reaction pressure is relatively high.

[0004] Therefore, how to design a high-performance catalyst to prepare N-(3-aminopropyl)cyclohexylamine by catalytic hydrogenation with high activity, high selectivity and high stability using ethyl cyclohexylamine as a raw material under relatively mild conditions is still an urgent problem to be solved. Summary of the invention

[0005] The invention aims to provide a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenating nitrileethylcyclohexylamine, a preparation method and application thereof, so as to improve the catalytic hydrogenation activity, selectivity and stability.

[0006] In order to solve the above technical problems, the present invention first discloses a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine. The catalyst comprises an active component, an auxiliary component and a carrier. The active component is Co, the auxiliary component is Mg, and the carrier is alumina. The catalyst presents a one-dimensional hollow nanotube structure.

[0007] Furthermore, the active component is 25%-80% by mass of Co; the auxiliary component is 0.05%-25% by mass of Mg; and the rest is carrier.

[0008] Furthermore, the active component is 55%-70% by mass of Co; the auxiliary component is 0.1%-2% by mass of Mg; and the rest is carrier.

[0009] The present invention also discloses a method for preparing the catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine as described above.

[0010] The catalyst is prepared by the following steps:

[0011] (I) dispersing carbon nanotubes with oxygen-containing functional groups in deionized water at room temperature, and vigorously stirring at 400-500 rpm for 3-5 hours to obtain a mixed solution;

[0012] (II) dissolving a soluble salt of Co, a soluble salt of Mg, a soluble salt of Al, and a hydroxylamino ligand in the mixed solution obtained in step (I), heating the mixture to 50-80° C. and vigorously stirring the mixture at 400-500 rpm for 1-3 hours to obtain a mixed solution;

[0013] (III) The mixed solution obtained in step (II) is cooled to room temperature, urea is dissolved in the mixed solution, and the mixture is vigorously stirred at 400-500 rpm for 0.5-1 h to obtain a mixture;

[0014] (IV) transferring the mixture obtained in step (III) into a sealed pressure-resistant hydrothermal autoclave, heating it to 100-180° C. and treating it for 10-24 hours; filtering it with suction, washing it with deionized water until the filtrate is neutral, and drying it in an oven at 100-120° C. for 10-14 hours to obtain a dried solid;

[0015] (V) crushing the solid obtained in step (IV) into small particles of 60-150 mesh, and calcining in a muffle furnace, the temperature rise rate of the muffle furnace being 1-5°C / min, the calcination temperature being 350-600°C, and the calcination time being 3-10 h, to obtain a calcined solid;

[0016] (VI) activating the solid obtained in step (V) in a reduction activation furnace, wherein the reduction activation gas is hydrogen or a mixture of hydrogen and an inert gas, the heating rate is 2-5°C / min, the activation temperature is 500-650°C, the activation time is 2-10 h, and after cooling to room temperature, passivation treatment is performed to obtain the catalyst.

[0017] Furthermore, the carbon nanotubes in step (I) have oxygen-containing functional groups.

[0018] Furthermore, the oxygen-containing functional group is one or more of a hydroxyl group, a carboxyl group or a carbonyl group.

[0019] Furthermore, in step (II), the soluble salt of Co is one of cobalt chloride, cobalt sulfate, cobalt nitrate, and cobalt acetate, the soluble salt of Mg is one of magnesium nitrate and magnesium chloride, and the soluble salt of Al is aluminum nitrate; and the hydroxylamino ligand is one of hydroxypropylamine, hydroxybutylamine, and hydroxyhexylamine.

[0020] Furthermore, the molar ratio of the hydroxylamino ligand to the Co metal ion is greater than 1:1; the molar ratio of urea to the total metal ions is 3.5-4:1, preferably 3.76:1.

[0021] Furthermore, in the total mass of the carbon nanotubes, the soluble salt of Co, the soluble salt of Mg, and the soluble salt of Al, the carbon nanotubes account for 10-50%.

[0022] The present invention also discloses an application of the catalyst as described above or the catalyst prepared by the method as described above in hydrogenating ethyl cyclohexylamine to prepare N-(3-aminopropyl) cyclohexylamine. The catalyst is first loaded into a micro-packed bed reactor, and the entire reaction tube of the micro-packed bed reactor is filled with quartz sand. The reaction is adjusted to a specified reaction condition, and a mixture of ethyl cyclohexylamine and methanol is pumped in. The mass concentration of ethyl cyclohexylamine in the mixture of ethyl cyclohexylamine and methanol is 3-15%. The reaction conditions are: reaction temperature of 30-100°C, reaction pressure of 0.5-2.0 MPa, and liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol of 0.05-1.0h -1 , the molar ratio of hydrogen to ethyl cyclohexylamine is 1.1:1-2:1.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention uses nitrile ethyl cyclohexylamine as a raw material to prepare N-(3-aminopropyl) cyclohexylamine by hydrogenation. The intermediate C=N generated by the nitrile functional group during the hydrogenation reaction is active on the catalyst surface, and it is easy to condense to generate high-boiling point byproducts, or react with activated hydrogen free radicals to obtain primary amines. The high-performance nitrile hydrogenation catalyst prepared by the present invention has a hollow structure, and the active component and the auxiliary component are highly dispersed on the carrier surface, and there is a strong interaction between the metals. After the active component Co is reduced and activated, a zero-valent Co with activated hydrogen and nitrile functional groups is formed on the surface of the hollow nanotubes. When the activated hydrogen free radical is inserted into the nitrile functional group, the auxiliary component Mg on the catalyst surface inhibits the condensation process of the intermediate species C=N, thereby promoting the generation of the target product primary amine. In the catalyst synthesis process, the present invention first uses the strong interaction between the hydroxylamino ligand and the oxygen-containing functional groups on the surface of the carbon nanotube to anchor the active metal Co precursor, that is, Co forms a deposition around the carbon nanotube, and then uses the hydrothermal effect under alkaline conditions to deposit Mg-Al species around Co to form a close contact interface of Co-Mg-Al. The highly dispersed metal interface is the main reason for its high activity, high selectivity and high stability. In addition, in the catalyst synthesis process, carbon nanotubes are used as hard templates, which can not only promote the high dispersion of active species and auxiliary agent species, but also form a one-dimensional hollow structure. The one-dimensional hollow structure can form a high concentration aggregation of reactants in a microscopic scale during the reaction process, thereby improving its catalytic reaction effect.

[0025] 2. The high-performance cobalt-based heterogeneous catalyst prepared by the present invention has the advantages of stable structure, high mechanical strength, good thermal conductivity, high substrate conversion rate (100%) and excellent product selectivity (above 96.6%).

[0026] The catalyst preparation method of the invention has good repeatability and low raw material price, and can significantly reduce the cost in the current N-(3-aminopropyl)cyclohexylamine synthesis process. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a SEM image of the catalyst of Example 1;

[0028] Figure 2 is a catalyst stability test diagram of Example 1;

[0029] Figure 3 It is the product chromatogram of Example 1. DETAILED DESCRIPTION

[0030] The present invention is further explained below in conjunction with the examples and drawings. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0031] Example 1

[0032] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0033] (II) 1.45 g Co(NO 3 ) 2 6H 2 O (4.98 mmol), 0.64 g Mg(NO 3 ) 2 6H 2 O (2.50mmol), 0.93g Al(NO 3 ) 3 9H 2 O (2.48 mmol) and 1.2 g of hydroxypropylamine (15.98 mmol) were dissolved in the mixed solution obtained in step (I), the temperature was raised to 50 °C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution.

[0034] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea (37.46 mmol) was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0035] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0036] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0037] (VI) The solid obtained in step (V) was activated at 550° C. for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2° C. / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 1-CoMg / Al 2 O 3 .

[0038] The catalyst prepared in this example is 1-CoMg / Al 2 O 3 , Figure 1 It is shown that the catalyst has a one-dimensional hollow nanotube structure.

[0039] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling and entering gas chromatography analysis, the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 98.2%.

[0040] Example 2

[0041] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0042] (II) 1.45 g Co(NO 3 ) 2 6H 2 O, 0.96 g Mg(NO 3 ) 2 6H 2 O, 0.46 g Al(NO 3 ) 3 9H 2 O, 1.2 g of hydroxypropylamine was dissolved in the mixed solution obtained in step (I), the temperature was raised to 50 °C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution;

[0043] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0044] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0045] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0046] (VI) The solid obtained in step (V) was activated at 550°C for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2°C / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 2-CoMg / Al 2 O3 .

[0047] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling and entering gas chromatography analysis, the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 98%.

[0048] Example 3

[0049] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0050] (II) 1.45 g Co(NO 3 ) 2 6H 2 O (4.98 mmol), 0.32 g Mg(NO 3 ) 2 6H 2 O (1.25 mmol), 1.4 gAl(NO 3 ) 3 9H 2 O (3.73 mmol) and 1.2 g hydroxypropylamine (15.98 mmol) were dissolved in the mixed solution obtained in step (I), the temperature was raised to 50 °C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution;

[0051] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea (37.46 mmol) was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0052] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0053] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0054] (VI) The solid obtained in step (V) was activated at 550° C. for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2° C. / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 3-CoMg / Al 2 O 3 .

[0055] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling and entering gas chromatography analysis, the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 98.8%.

[0056] Example 4

[0057] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0058] (II) 1.45 g Co(NO 3 ) 2 6H 2 O, 0.03 g Mg(NO 3 ) 2 6H 2 O, 1.821 g Al(NO 3 ) 3 9H 2 0.1.2 g of hydroxypropylamine was dissolved in the mixed solution obtained in step (I), the temperature was raised to 50°C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution;

[0059] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0060] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0061] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0062] (VI) The solid obtained in step (V) was activated at 550°C for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2°C / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 4-CoMg / Al 2 O 3 .

[0063] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling and entering gas chromatography analysis, the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 99.5%.

[0064] Example 5

[0065] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0066] (II) 1.25 g (CH 3 COO 2 Co·4H 2 O, 0.64 g Mg(NO 3 ) 2 6H 2 O, 0.93 g Al(NO 3 ) 3 9H 2 0.1.2 g of hydroxypropylamine was dissolved in the mixed solution obtained in step (I), the temperature was raised to 50°C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution;

[0067] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0068] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0069] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0070] (VI) The solid obtained in step (V) was activated at 550°C for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2°C / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 5-CoMg / Al 2 O 3 .

[0071] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling, gas chromatography analysis showed that the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 97.9%.

[0072] Example 6

[0073] (I) At room temperature, 1.3 g of carbon nanotubes with oxygen-containing functional groups were dispersed in 50 mL of deionized water and vigorously stirred at 400 rpm for 3 h to obtain a mixed solution.

[0074] (II) 1.19 g CoCl 2 6H 2 O, 0.64 g Mg(NO 3 ) 2 6H 2 O, 0.93 g Al(NO 3 ) 3 9H 2 0.1.2 g of hydroxypropylamine was dissolved in the mixed solution obtained in step (I), the temperature was raised to 50°C and stirred vigorously at 400 rpm for 1 h to obtain a new mixed solution;

[0075] (III) The mixed solution obtained in step (II) was cooled to room temperature, 2.25 g of urea was dissolved in the mixed solution cooled to room temperature, and the mixture was vigorously stirred at 400 rpm for 0.5 h to obtain a mixture.

[0076] (IV) The mixture obtained in step (III) is transferred to a sealed pressure-resistant hydrothermal autoclave, heated to 100°C and treated for 24 hours; filtered and washed until the filtrate is neutral, and dried in an oven at 120°C for 12 hours to obtain a dried solid.

[0077] (V) The solid obtained in step (IV) is crushed into small particles of 60-150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace is 2 °C / min, the calcination temperature is 400 °C, and the calcination time is 5 h to obtain a calcined solid.

[0078] (VI) The solid obtained in step (V) was activated at 550°C for 3 h in a reduction activation furnace, the reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen volume content was 10%), the heating rate was 2°C / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst 5-CoMg / Al 2 O 3 .

[0079] Take 1.0 g of the above catalyst and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand. Adjust the reaction temperature to 90 °C, the reaction pressure to 1.0 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine is 5%) to 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling, gas chromatography analysis showed that the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 97.9%.

[0080] Example 7

[0081] 1.0 g of the catalyst in Example 4 was loaded into a fixed bed reactor, and the entire reaction tube of the reactor was filled with quartz sand. The reaction temperature was adjusted to 90° C., the reaction pressure was 1.5 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine was 5%) was 0.3 h -1 The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling, gas chromatography analysis showed that the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 97.5%.

[0082] Example 8

[0083] 1.0 g of the catalyst in Example 4 was loaded into a fixed bed reactor, and the entire reaction tube was filled with quartz sand. The reaction temperature was adjusted to 90° C., the reaction pressure was 2 MPa, and the liquid hourly space velocity of the mixture of ethyl cyclohexylamine and methanol (the mass concentration of ethyl cyclohexylamine was 5%) was 0.3 h -1The molar ratio of hydrogen to ethyl cyclohexylamine was 1.3:1. After sampling, gas chromatography analysis showed that the conversion rate of ethyl cyclohexylamine was 100%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 96.6%.

[0084] Example 9

[0085] The catalyst in Example 4 was used for experimental stability test of the product N-(3-aminopropyl)cyclohexylamine. The catalyst performance analysis showed that no obvious deactivation of the catalyst was found after 200 hours of reaction. Figure 2 This indicates that when the product is N-(3-aminopropyl)cyclohexylamine, the catalyst has excellent stability.

[0086] Comparative Example 1

[0087] CoMg / Al was prepared by conventional coprecipitation method 2 O 3 The specific steps are as follows: 4.93 g Co(NO 3 ) 2 6H 2 O, 0.57 g Mg(NO 3 ) 2 6H 2 O, 7.84 g Al(NO 3 ) 3 9H 2 O, 3.64g hydroxypropylamine, recorded as solution A; then use 100mL deionized water to dissolve 8g NaOH, 5.2g Na 2 CO 3 , recorded as solution B. Solution B was then added dropwise to solution A at a speed of 100 rpm until the pH of the solution was 10, and then placed in a 90°C water bath for aging for 6 hours, followed by suction filtration. When the filtrate was neutral, the mixture was placed in a 100°C oven for 6 hours, and the resulting solid was crushed into small particles below 150 mesh and then calcined in a muffle furnace. The heating rate of the muffle furnace was 2°C / min, the calcination temperature was 400°C, and the calcination time was 5 hours. The resulting solid was activated at 550°C in a reduction activation furnace for 3 hours. The reduction activation gas was a mixture of hydrogen and nitrogen (hydrogen content was 10%), the heating rate was 2°C / min, and after cooling to room temperature, passivation treatment was performed to obtain the catalyst A-CoMg / Al 2 O 3 .

[0088] 1.0 g of the above catalyst was loaded into a packed bed reactor, and the entire reaction tube was filled with quartz sand. The reaction temperature was adjusted to 90°C, the reaction pressure was 1.0 MPa, the liquid hourly space velocity of the mixture of ethylcyclohexylamine and methanol (the mass concentration of ethylcyclohexylamine was 5%) was 0.3 h-1, and the molar ratio of hydrogen to ethylcyclohexylamine was 1.3:1. After sampling, gas chromatography analysis was performed, and the conversion rate of ethylcyclohexylamine was 73%, and the selectivity of the target product N-(3-aminopropyl)cyclohexylamine was 82.5%.

[0089] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrile ethylcyclohexylamine, characterized in that: The catalyst comprises an active component, an auxiliary component and a carrier, wherein the active component is Co, the auxiliary component is Mg, and the carrier is alumina. The catalyst presents a one-dimensional hollow nanotube structure.

2. The catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine according to claim 1, characterized in that: The active component is calculated based on the mass of Co single substance, and its content is 25%-80%; the auxiliary component is calculated based on the mass of Mg single substance, and its content is 0.05%-25%; and the rest is carrier.

3. The catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrile ethylcyclohexylamine according to claim 2, characterized in that: The active component is calculated based on the mass of Co single substance, and its content is 55%-70%; the auxiliary component is calculated based on the mass of Mg single substance, and its content is 0.1%-2%; and the rest is carrier.

4. A method for preparing a catalyst for hydrogenating nitrileethylcyclohexylamine to prepare N-(3-aminopropyl)cyclohexylamine as claimed in any one of claims 1 to 3, characterized in that: The catalyst is prepared by the following steps: (I) dispersing carbon nanotubes with oxygen-containing functional groups in deionized water at room temperature, and vigorously stirring at 400-500 rpm for 3-5 hours to obtain a mixed solution; (II) dissolving a soluble salt of Co, a soluble salt of Mg, a soluble salt of Al, and a hydroxylamino ligand in the mixed solution obtained in step (I), heating the mixture to 50-80° C. and vigorously stirring the mixture at 400-500 rpm for 1-3 hours to obtain a mixed solution; (III) The mixed solution obtained in step (II) is cooled to room temperature, urea is dissolved in the mixed solution, and the mixture is vigorously stirred at 400-500 rpm for 0.5-1 h to obtain a mixture; (IV) transferring the mixture obtained in step (III) into a sealed pressure-resistant hydrothermal autoclave, heating it to 100-180° C. and treating it for 10-24 hours; filtering and washing until the filtrate is neutral, and drying it in an oven at 100-120° C. for 10-14 hours to obtain a dried solid; (V) crushing the solid obtained in step (IV) into small particles of 60-150 mesh, and calcining in a muffle furnace, the temperature rise rate of the muffle furnace being 1-5°C / min, the calcination temperature being 350-600°C, and the calcination time being 3-10 h, to obtain a calcined solid; (VI) activating the solid obtained in step (V) in a reduction activation furnace, wherein the reduction activation gas is hydrogen or a mixture of hydrogen and an inert gas, the heating rate is 2-5°C / min, the activation temperature is 500-650°C, the activation time is 2-10 h, and after cooling to room temperature, passivation treatment is performed to obtain the catalyst.

5. The method for preparing a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine according to claim 4, characterized in that: The carbon nanotubes in step (I) have oxygen-containing functional groups.

6. The method for preparing a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine according to claim 5, characterized in that: The oxygen-containing functional group is one or more of a hydroxyl group, a carboxyl group or a carbonyl group.

7. The method for preparing a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine according to claim 4, characterized in that: In step (II), the soluble salt of Co is one of cobalt chloride, cobalt sulfate, cobalt nitrate, and cobalt acetate; the soluble salt of Mg is one of magnesium nitrate and magnesium chloride; the soluble salt of Al is aluminum nitrate; and the hydroxylamino ligand is one of hydroxypropylamine, hydroxybutylamine, and hydroxyhexylamine.

8. The method for preparing a catalyst for hydrogenating nitrile ethylcyclohexylamine to prepare N-(3-aminopropyl)cyclohexylamine according to claim 7, characterized in that: The molar ratio of the hydroxylamino ligand to the Co metal ion is greater than 1:1; the molar ratio of urea to the total metal ions is 3.5-4:

1.

9. The method for preparing a catalyst for preparing N-(3-aminopropyl)cyclohexylamine by hydrogenation of nitrileethylcyclohexylamine according to claim 4, characterized in that: The carbon nanotubes account for 10-50% of the total mass of the carbon nanotubes, the soluble salt of Co, the soluble salt of Mg, and the soluble salt of Al.

10. Use of a catalyst according to any one of claims 1 to 3 or a catalyst prepared by the method according to any one of claims 4 to 9 in the hydrogenation of nitrileethylcyclohexylamine to prepare N-(3-aminopropyl)cyclohexylamine, characterized in that: First, the catalyst is loaded into a micro-packed bed reactor, and the entire reaction tube of the micro-packed bed reactor is filled with quartz sand. The reaction conditions are adjusted to the specified reaction conditions, and a mixture of ethylcyclohexylamine and methanol is pumped in. The mass concentration of ethylcyclohexylamine in the mixture of ethylcyclohexylamine and methanol is 3-15%. The reaction conditions are: reaction temperature 30-100° C., reaction pressure 0.5-2.0 MPa, liquid hourly space velocity of the mixture of ethylcyclohexylamine and methanol 0.05-1.0 h -1 , the molar ratio of hydrogen to ethyl cyclohexylamine is 1.1:1-2:1.